Road vehicle automation 2 - Meyer, Gereon; Beiker, Sven; SpringerLink (Online service).; Automated Vehicle Symposium Burlingame, Calif.) (2014. (Cham Springer International Publishing, 2015)
This paper collection is the second volume of the LNMOB series on Road Vehicle Automation. The book contains a comprehensive review of current technical, socio-economic, and legal perspectives written by experts coming from public authorities, companies and universities in the U.S., Europe and Japan. It originates from the Automated Vehicle Symposium 2014, which was jointly organized by the Association for Unmanned Vehicle Systems International (AUVSI) and the Transportation Research Board (TRB) in Burlingame, CA, in July 2014. The contributions discuss the challenges arising from the integration of highly automated and self-driving vehicles into the transportation system, with a focus on human factors and different deployment scenarios. This book is an indispensable source of information for academic researchers, industrial engineers, and policy makers interested in the topic of road vehicle automation.
Part I Public Sector Activities -- Part II Industrial Research and Innovation -- Part III Human Factors and Challenges -- Part IV Legal, Business and Systemic Perspectives -- Part V Vehicle Systems and Technologies Development -- Part VI Transportation Infrastructure and Planning.
Electronic reproduction.
Keywords: Motor vehicles -- Automatic control -- Congresses; Autonomous vehicles -- Congresses; Intelligent transportation systems -- Congresses; Electronic books